2018
DOI: 10.31234/osf.io/k9y7s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do women's preferences for masculine voices shift across the ovulatory cycle?

Abstract: Are estrous mate preference shifts robust? This question is the subject of controversy within human evolutionary sciences. For nearly two decades, mate preference shifts across the ovulatory cycle were considered an important feature of human sexual selection, directing women’s attention towards mates with indicators of “good genes” in their fertile phase, when conception is possible. However, several recent studies on masculine faces, bodies or behaviors have failed to find evidence supporting this account, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Further, between-subject designs with small sample sizes were also methodological concerns in early studies of menstrual cycle effects on women’s mate preferences 46 . While some studies that measured women’s hormones to characterize current fertility reported women’s preferences for masculine characters were stronger when conception is more likely 47 , several recent studies have found no change in mate preferences among women at the peri-ovulatory phase for muscularity 48,49 , facial masculinity 23,49,50 , beards 23,51 , vocal masculinity 52,53 and facial symmetry 49 . Thus, the extent to which ovulatory cycle shifts are associated with women’s mate preferences may have been overestimated in past research due to imprecise methodologies and small sample sizes 54 .…”
Section: Introductionmentioning
confidence: 98%
“…Further, between-subject designs with small sample sizes were also methodological concerns in early studies of menstrual cycle effects on women’s mate preferences 46 . While some studies that measured women’s hormones to characterize current fertility reported women’s preferences for masculine characters were stronger when conception is more likely 47 , several recent studies have found no change in mate preferences among women at the peri-ovulatory phase for muscularity 48,49 , facial masculinity 23,49,50 , beards 23,51 , vocal masculinity 52,53 and facial symmetry 49 . Thus, the extent to which ovulatory cycle shifts are associated with women’s mate preferences may have been overestimated in past research due to imprecise methodologies and small sample sizes 54 .…”
Section: Introductionmentioning
confidence: 98%
“…The measures obtained were mean f o , the first four formant frequencies (F 1 -F 4 ), four measures of jitter and five measures of shimmer. Because both jitter (all rs > 0.83, ps < 0.001) and shimmer measures (all rs > 0.56, ps < 0.001) were highly intercorrelated, a standardized mean was calculated for each perturbation measure 10 . Additionally, P f was computed for the first four formants 6 .…”
Section: Design and Methodsmentioning
confidence: 99%
“…According to the source-filter theory, f o and P f are theoretically distinct 91 . They are also only weakly correlated 10 and seem to convey different information about a male speaker 6 . Accordingly, we predicted f o and P f to be independent predictors of both attractiveness (H7) and dominance (H8) ratings.…”
Section: Perceptions Of Attractiveness and Dominancementioning
confidence: 99%
“…These studies have reported mixed results, potentially because they were generally particularly badly underpowered [34] and/or because the substantial genetic variation in mate preferences [39] There has recently been a concerted effort by many researchers to address these potentially important methodological limitations. For example, several recent large-scale, within-subject studies have investigated women's preferences for facial masculinity [40][41][42], beardedness [42,43], body masculinity [41,44], facial symmetry [41], or vocal masculinity [45] using luteinizing hormone (LH) tests and/or other hormone measures to confirm the timing and occurrence of ovulation. Notably, none of these studies observed significant effects of fertility on women's preferences for masculine or symmetric men.…”
Section: Methodological Problems With Previous Researchmentioning
confidence: 99%